Digital-based Education Marketing in Achieving Customer Satisfaction in Madrasa Tsanawiyah - Ranosa, M. Risky; Fauzan, Ahmad; Ayu, Sovia Mas; Koderi, Koderi (Journal of Advanced Islamic Educational Management, 2023)
The process of providing data information in an easy, fast, meaningful, global, sustainable and meaningful way by madrasas to customer satisfaction which is really needed through a digital basis. This study aims to analyze and describe digital-based communication, distribution and educational services in madrasa tsanawiyah. The approach used is naturalistic phenomenology, with descriptive qualitative methods. Collecting data with interview techniques, observation and documentation. Data analysis by reducing data, displaying data and drawing conclusions. Test the validity of the data by using triangulation techniques and sources. The results of this study indicate that Madasa Tsanawiyah Negeri 2 Bandar Lampung has carried out digital marketing of education in the form of related information 1) Communication of MTs N 2 Bandar Lampung is carried out by paying attention to what is the customer's need, in which communication is published through information on student achievements and is useful for archiving data the basic considerations are the values that exist in the vision and mission and goals of the madrasa by forming a team. 2) Distribution by publishing on digital media regarding the location and strategic location of madrasas, the use of places and locations for positive activities which are carried out by developing the use of information technology-based facilities. 3) The service focuses on accepting new students for the publication of MTs N 2 Bandar Lampung service programs, which are in the form of digital registration, manual registration and then announcements via digital. Digital marketing at MTs N 2 Bandar Lampung has also carried out digital marketing of education according to Islam where the head of the madrasa implements the traits exemplified by the Prophet Muhammad in doing business, including sidiq, amanah, tabligh and fatonah accompanied by ethical principles.